EN TORNO A LA TRADUCCIÓN DE UN RELATO DE MAUPASSANT: SUR L´EAU - Ozaeta Gálvez, Mª Rosario (Anales de Filología Francesa, 2007)
Sur l’eau, a short story by Maupassant, was meant to be included in a diary with two other travel tales (Au soleil, La vie errante), but the author never finished it. It preserves, however, its autobiographical nature, and it is, as a matter of fact, the most representative of the author’s personality. Its most revealing traits can be made out clearly as the story unfolds. In this study, the purpose is to examine the translation of Sur l’eau made by Leopoldo García Ramón, a versatile writer and translator, showing its most representative characters, described with examples of the translated text. The analysis is preceded by an exhaustive presentation on the source text and the figure of the translator, aiming to place both in their respective contexts.